FISCAL REFORM IMPACT ON STRENGTHENING LOCAL GOVERNMENT FINANCIAL BASIS - Goncharenko M.V. (Pressing Problems of Public Administration, 2015)
The paper examines major changes in the national budgetary laws and mechanisms of theirimplementation for decentralization of finances. Positive and negative aspects of the Ukrainianfiscal reform’s impact on strengthening the financial basis of local governments are studied.